Insulin Resistance Estimated by HOMA IR for Diagnosis of Gestational Diabetes in Squatter Settlement of Karachi - Hira Attique; Syed Tousif Ahmed; Rehana Rehman; Shahina Ishtiaque; Saeeda Baig (ziauddin University, 2020)
Background: Gestational diabetes mellitus (GDM), one of the most common metabolic disorders of pregnancy, is estimated to raise 16-27% worldwide every 10 years. Researchers, using Homeostasis model assessment test (HOMA IR), a tool for assessing insulin resistance, have found a number of causes. This study was designed to investigate the correlation between insulin resistance and GDM in the second trimester. Methods: This study recruited 84 pregnant women (24 to 28 weeks of gestation) from OPD of Gynaecology/Obstetrics and Family Medicine Department, Dr. Ziauddin Hospital Karachi Pakistan from May 2018 to January 2019. A thorough anthropometric measurements and antenatal history was recorded through structured questionnaire after informed consent. After 10 hours fast, venous blood (5ml) was drawn for fasting blood glucose (FBS), insulin levels and Glucose challenge test (GCT) for screening gestational diabetes. Results: Out of 84 subjects, 37 had higher GCT values while 47 had normal level. FBS was found significantly associated (p < 0.05). With GCT among GDM subjects 16(19%) had normal Body Mass Index (BMI) and 18(21.4%) had normal body fat percentage however, 2(2.4%) had high insulin levels and 13(15.5%) high FBS levels. The value HOMA IR, ≤1.29 was found in 38(45.2) healthy mothers and 25(29.8) GDM. Patients' GCT had positive association with parity, FBS, insulin, HOMA IR and BMI. Conclusion: Linear strong positive correlation was found between insulin resistance and GCT in the second trimester. Patients with significantly higher GCT values and index value of HOMA IR greater than >1.29 are at risk for developing GDM.